Initial Cost Comparison of Rigid and Flexible Pavements Case Study: Khartoum State (University of Khartoum Engineering Journal, 2022)
n Sudan, only flexible pavements are used despite some doubts regarding their economic value underdifferent conditions. In this paper, the properties and design of cement concrete rigid pavement and flexible pavementwere described. The initial costs of both types of pavements were compared, based on the prices of the Ministry ofInfrastructures and Transportation, Khartoum State. While the soil sub-grade and traffic loading govern the pavementdesign, the material composition is the most relevant factor in the comparison. Although only the initial cost was usedfor the comparison, it was found that rigid pavements were more economical than flexible pavements regardless ofsubsoil conditions for traffic volume less than 3,000,000 ESAL. The preference of rigid pavements will definitely bemore beneficial when the total life cycle cost is considered. It is advisable for road authorities to develop parametricguidelines regarding the selection of pavement type.